The Influence Of Competence, Integrity And Organizational Culture On Employee Performance In Job Satisfaction Moderation At Bank Indonesia Provincial Representative Offices North Sumatra - Rudi Herbet Sianturi; Mesra B (International Journal of Management, Economic and Accounting, 2024)
Various resources, including people, money, machines, equipment, and information resources, are required to achieve the organization's goals. Human resource management is very important for the organization, so in managing it, managing and utilizing human resources will run according to what is expected, so that it can function productively to achieve organizational goals. This study was conducted to see the Influence of Competence, Integrity and Organizational Culture on Employee Performance in Job Satisfaction Moderation at the Bank Indonesia Representative Office in North Sumatra Province. The results of this study are as follows: Organizational Culture has a positive and significant effect on Employee Performance with a value of 0.366 and a significant 0.000. Job Satisfaction is not able to moderate Competency on Employee Performance with a value of 0.038 to a significant 0.129. Job Satisfaction was able to moderate Integrity to Employee Performance with a value of -0.127 significant 0.013. Job Satisfaction is able to moderate Organizational Culture towards Employee Performance with a value of 0.120 and a significant 0.023. Integrity has a positive and significant effect on Employee Performance with a value of 0.397 and a significant 0.000. Job Satisfaction has a positive and significant effect on Employee Performance with a value of 0.278 significant 0.000. Competence had a positive and insignificant effect on Employee Performance with a value of 0.007 to a significant 0.377.